Pengaruh Pengetahuan Audit dan Pengalaman Audit Terhadap Kualitas Audit pada Inspektorat Provinsi Gorontalo - Virginia; Gaffar; Mattoasi (Economic Reviews Journal, 2024)
This research aims to determine the influence of audit knowledge and audit experience on audit quality at the Gorontalo Province Inspectorate. The data used in this research is primary data sourced from 53 Gorontalo Province Inspectorate Respondents. This research uses Structur Equation Modeling Partial Least Square (SEM-PLS) analysis. The results of this research show that 1). Audit Knowledge has a positive and insignificant effect on Audit Quality at the Gorontalo Province Inspectorate. This means that every increase in Audit Knowledge cannot improve Audit Quality. This cannot be explained in real terms. 2). Audit experience has a positive and significant effect on Audit Quality at the Gorontalo Province Inspectorate. This means that every increase in Audit Experience can improve Audit Quality. This can be explained in real terms.